2015
DOI: 10.1039/c5ra15876a
|View full text |Cite
|
Sign up to set email alerts
|

High temperature dielectric relaxation anomalies in Ca0.9Nd0.1Ti0.9Al0.1O3−δsingle crystals

Abstract: We herein report dielectric studies on Ca0.9Nd0.1Ti0.9Al0.1O3−δ single crystals grown by the optical floating zone technique in the temperature range from room temperature to 660 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Electrical inhomogeneities could be the possible reason for these high temperature dielectric relaxations. 72 The results obtained in this study indicate that our ceramics are of extreme signicance as far as their technological and industrial applications are concerned.…”
Section: Resultsmentioning
confidence: 66%
“…Electrical inhomogeneities could be the possible reason for these high temperature dielectric relaxations. 72 The results obtained in this study indicate that our ceramics are of extreme signicance as far as their technological and industrial applications are concerned.…”
Section: Resultsmentioning
confidence: 66%
“…15 The high permittivity (3 0 ) and low dielectric loss (tan d) of CaTiO 3 make it suitable for microwave dielectric applications as lters and resonators. 16,17 From the Xray diffraction, it was observed that calcium titanate (CaTiO 3 ) has a distorted orthorhombic structure. At room temperature, CaTiO 3 has a paraelectric phase.…”
Section: Introductionmentioning
confidence: 99%